Rancang Bangun Aplikasi E-Learning Berbasis Web Di Sekolah Pendidikan Non Formal Sanggar Kegiatan Belajar Kota Palangka Raya - Widiatry, Widiatry; Isachar, Michael (Universitas Palangka Raya, 2021)
The development of information technology in the field of education, especially in the SKB (Study of Learning Activities) in the city of Palangka Raya requires e-learning applications to increase the effectiveness and flexibility of learning, because in this Learning Activity Studio it is still conventional, namely the learning process is still by teaching between students with This can only be done with the condition that there is a meeting between students and teachers in the classroom. This school is included in non-formal education which has the aim of replacing, adding to, and complementing formal education.The development method used by the author is the waterfall method in conducting this research. The waterfall method is a method that uses a systematic and sequential approach starting from the level of defining system requirements to maintenance. Where the waterfall method has 6 phases, namely Requirement Specification, Architectural Design, Coding, Integration & Testing, Operation & Maintenance.The results achieved are the availability of applications to support teaching and learning activities that can be obtained without being bound by time and place. The conclusion with this web-based e-learning is that it facilitates teacher and student communication, provides material, facilitates assignment and collection of assignments, and facilitates value information.